Fund Flows and Market States - Franzoni, Francesco; Schmalz, Martin C. (Review of Financial Studies, 2017)
This paper establishes a new empirical fact: Mutual funds’ flow-performance sensitivity is a hump-shaped function of aggregate risk-factor realizations. Explanations based on extant theories can explain only a fraction of the pattern. We thus develop a new parsimonious model. It assumes Bayesian investors who are uncertain about the degree to which fund returns are exposed to systematic risk. Fund performance is then less informative about manager skill when factor realizations are larger in absolute value. The data also support the out-of-sample prediction that the hump shape is more pronounced for funds with more uncertain risk loadings.Received October 24, 2014; editorial decision October 11, 2016 by Editor Itay Goldstein.